Effect of Microwave Treatment on Sinapic Acid Derivatives in Rapeseed and Rapeseed Meal. (27th November 2012) - Niu, Yanxing; Jiang, Mulan; Wan, Chuyun; Yang, Mei; Hu, Shuangxi
Abstract: Microwave treatment is a new method for rapeseed processing. To better understand the benefits of microwave pretreatment on rapeseed processing, qualitative and quantitative analysis of sinapic acid derivatives is needed. In this study, the effect of microwave treatment on the content of sinapic acid derivatives in rapeseed and the effect of cold‐press and solvent extraction on the content of sinapic acid derivatives in rapeseed meal were evaluated using ultrahigh pressure liquid chromatography. It was found that during the microwave treatment, the content of sinapine and sinapic acid in the rapeseed increased slightly at the outset of treatment and significantly decreased thereafter. Following 7 min of microwave treatment, the content of sinapine in rapeseed exhibited its largest decrease of 16.7 %. By contrast, microwave heating of the rapeseed increased the canolol content significantly. We employed two sample paired t tests as a means to analyze the difference between meal and defatted cold‐pressed cake. The results indicated that the content of sinapine and sinapic acid in defatted cake was significantly higher than that in meal, while the different extraction methods (solvent extraction and cold‐press) did not appear to have a significant influence on the content of canolol in meal ( p ≤ 0.05).